2019
DOI: 10.1186/s13068-019-1377-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing co-translational folding of heterologous protein by deleting non-essential ribosomal proteins in Pichia pastoris

Abstract: Background Translational regulation played an important role in the correct folding of heterologous proteins to form bioactive conformations during biogenesis. Translational pausing coordinates protein translation and co-translational folding. Decelerating translation elongation speed has been shown to improve the soluble protein yield when expressing heterologous proteins in industrial expression hosts. However, rational redesign of translational pausing via synonymous mutations may not be feasib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Translational capacity or the availability of amino acids may represent a general limitation for yeasts during recombinant protein production, therefore. 2325 This hypothesis is corroborated by another engineered strain with an upregulated translation factor that exhibited with improved secreted productivity by expanding the cellular capacity for translation. 26 Strategies to further redirect translational capacity towards the recombinant product of interest warrant further investigation.…”
Section: Discussionmentioning
confidence: 79%
“…Translational capacity or the availability of amino acids may represent a general limitation for yeasts during recombinant protein production, therefore. 2325 This hypothesis is corroborated by another engineered strain with an upregulated translation factor that exhibited with improved secreted productivity by expanding the cellular capacity for translation. 26 Strategies to further redirect translational capacity towards the recombinant product of interest warrant further investigation.…”
Section: Discussionmentioning
confidence: 79%
“… 2011 , Liao et al . 2019 ). As the biosynthesis of ribosomal proteins has a connection with heterologous protein production, this could represent another potential reason for the effect of the TOM1 deletion.…”
Section: Resultsmentioning
confidence: 99%
“…Yeast ribosomal proteins play important roles in the biogenesis and function of the ribosome ( Aw et al, 2017 ). Deletion of a particular ribosome protein can delay or impair the subunit assembly, indicating that the decelerated elongation stage of translation might promote the co-translational folding rate of heterologous proteins ( Liao et al, 2019 ). In P. pastoris , overexpression of xylanase A (a foreign protein) can lead to a significant down-regulation of numerous ribosomal proteins, resulting in decelerated translation elongation and enhanced folding efficiency for xylanase A ( Navone et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…In P. pastoris , overexpression of xylanase A (a foreign protein) can lead to a significant down-regulation of numerous ribosomal proteins, resulting in decelerated translation elongation and enhanced folding efficiency for xylanase A ( Navone et al, 2021b ). Meanwhile, studies have shown that knocking out the C4QXU7 gene in P. pastoris does not affect its growth, but can lead to a significant increase in the secretion levels of exogenous proteins (e.g., Pfu and Phytase), indicating that the decelerated elongation rate caused by the loss of C4QXU7 might promote the co-translational folding rate of heterologous proteins, increasing the expression of Pfu and Phytase ( Liao et al, 2019 ). Together with our data on protein expression in P. pastoris , these observations could collectively indicate that knocking out the C4QXU7 gene may promote the expression of foreign proteins that are not easily folded in P. pastoris .…”
Section: Discussionmentioning
confidence: 99%